Stratonovich-type integral with respect to a general stochastic measure. Issue 7 (2nd October 2016) - Radchenko, Vadym
Abstract : Let be a general stochastic measure, where we assume for only -additivity in probability and continuity of paths. We prove that the symmetric integral is well defined. For stochastic equations with this integral, we obtain the existence and uniqueness of a solution.